Prognostic factors for percutaneous management of abdominal abscesses. Analysis of I 12 procedures - Andreoli, Gustavo (Cirugía del Uruguay, 2005)
Objectives: To study variables depending on intra-abdominal abscesses that render possib/e foretelling a favorable evolution consequent to its percutaneous drainage.